Algorithms for Parallelizing a Mathematical Model of Forest Fires on Supercomputers and Theoretical Estimates for the Efficiency of Parallel Programs; Cybernetics and Systems Analysis; Vol. 51, iss. 3 - Baranovskiy N. V. Nikolay Viktorovich (2015, 2015)
Title screen